PAHANG FLOOD DISASTER : THE POTENTIAL FLOOD DRIVERS - Rahmah Elfithri,; Syamimi Halimshah; Md Pauzi Abdullah; Mazlin Mokhtar,; Mohd Ekhwan Toriman; Ahmad Fuad Embi,; Maimon Abdullah; Maimon Abdullah (Malaysian Journal of Geosciences, 2017)
The northeast monsoon which occurs from November to March carries heavy rainfall which always result in flood especially to the east coast of Peninsular Malaysia. Pahang was one of the state that severely affected by this flood. Although the heavy rain is the main driver of the flood but human being cannot ignore the other flood drivers especially the river and its nearby environment circumstance which regard the flood event. The objective of this study was to determine the other flood drivers especially the river and its nearby environment circumstance which regard the flood event. The methodologies used in this study involved data collection through literature reviews and flood reports from Drainage and Irrigation Department (DID) and districts and interview to gather more information and verify the issues and other related drivers. The possible drivers of flooding in Pahang that occurred are as follows : 1) High rain intensity (>60 mm/hour, 200 – 450 mm/day) at the upstream that increases the quantity of water in the river and causes it to overflow 2) Water from area that has no drainage connection with the river (lowland, recessed and swamp area) was also flowing out and contributed to the flood 3) The size of the irrigation system is insufficient to bear the water flow rate and the tributary network is unable to withstand the large runoff 4) Increased reclaim of wetland area for development that causes irrigation system to be narrowed and obstructed for the water to flowing in to the tributaries 5) Prevalent forest clearing and logging activity increased the water non-absorbent area 6) Ground cutting for development purpose decreased the rain water absorption into the ground and increased surface water runoff, thus causes the watershed area decrease in its ability to hold water 7) Shallow estuary caused by high sedimentation from various activities leads to slow water conduction flowing from flood area to the sea 8) Most residential area are located at lowland and flood plain region coupled with bad irrigation system especially in big residential area, thus increased the flood risk. Each possible driver of flooding in Pahang that occurred in 2014 has to be discussed further in term of the responsible stakeholders who should involve in the management and maintenance. The heavy rainfall from northeast monsoon which was the main flood driver cannot be avoided but some flood drivers especially the river and its nearby environment that may contribute to higher magnitude of flood can be fixed and controlled by human